Pathways towards sustainable concrete. (April 2022) - Coffetti, D.; Crotti, E.; Gazzaniga, G.; Carrara, M.; Pastore, T.; Coppola, L.
Abstract: This paper covers a wide range of alternative strategies to improve the sustainability of concrete. It firstly considers the relatively easy application of the latest technologies to manufacture traditional Portland cement, including carbon capture, utilization and storage technologies, and the use supplementary cementitious materials as Portland cement replacement. It then focuses on more complex processes such as the substitution of traditional constituents with alternative binders (both non-Portland clinker or alkali-activated materials), recycled aggregates and non-drinking water, up to the description of high-durability/high performance mixtures. This review also underlines the significant need to upgrade the existing standards, and the relevance of thriving the education of designers, researchers and contractors for the development and the diffusion, also thanks to good practice, of new concrete technologies. This research also proposes a new sustainability index for mortars and concretes, also manufactured with negative carbon footprint materials, modifying the Empathetic Added Sustainability Index (EASI).